A CHILD CHARACTER'S DEVELOPMENT IN R.J. PALACIO'S CHILDREN'S REALISTIC FICTION NOVEL WONDER : A study of focalization - Nuriza, Rindra (2014)
Besides entertaining, children's literature is expected to stimulate children's understanding about particular values in real life and contributes to their development and needs. Due to this importance, many stories for children are delivered through realistic fiction. This paper thus aimed at investigating a child character's development in realistic fiction and identifying the contributions of focalization to the main character's development by using Bal's narratology (2009) as the main framework. To analyze data in the form of written texts, qualitative method with descriptive analysis was applied. The results showed that the main character developed through four key narrative events and different focalization. Both were examined to explicate the dynamic changes in his personalities and attitudes. The development was also contributed by the six characters' focalization which mostly revealed the shifts of direct and indirect speech, and the cognitive and perceptual views. This means that R.J. Palacio's Wonder is successful in portraying a realistic fiction picture of a deformed child. In consequence, it shows that multiple focalization opens horizon to different perspectives which is important in children's literature (Nikolajeva, 2002). Selain menghibur, sastra anak ditujukan untuk menstimulasi pemahaman anak tentang nilai-nilai tertentu dalam kehidupan nyata dan berkonstribusi terhadap kebutuhan dan perkembangan mereka. Berdasarkan kepentingan tersebut, banyak cerita dalam sastra anak disampaikan lewat fiksi reaslistis. Maka dari itu, penelitian ini bertujuan untuk menelaah perkembangan karakter anak dalam fiksi realistis dan mengidentifikasi kontribusi dari fokalisasi terhadap perkembangan tokoh utama dengan menggunakan teori naratif milik Bal (2009) sebagai teori dasar. Untuk menganalisis data dalam bentuk tulisan, digunakan metode kualitatif serta analisis secara deskriptif. Hasil penelitian menunjukan bahwa tokoh utama berkembang melalui empat kejadian utama dan beragam fokalisasi. Keduanya ditelaah untuk memperjelas perubahan dinamis dalam sikap dan tingkah laku. Perkembangan tersebut juga dibantu oleh fokalisasi dari enam karakter yang umumnya menunjukan pergantian antara ujaran langsung dan tidak langsung, dan pandangan kognitif dan perseptual. Ini membuktikan bahwa Wonder karya R.J. Palacio berhasil melukiskan gambaran realistis tentang seorang anak cacat. Hasilnya, penemuan tersebut memperlihatkan bahwa ragam fokalisasi membuka horison terhadap pandangan-pandangan berbeda yang penting dalam sastra anak (Nikolajeva, 2002)